METHODS OF ADMINISTRATION OF ANTIHELMINT PREPARATIONS AGAINST HELMINTHOUS DISEASES OF FISH (Scientific journal of the Fergana State University, 2023)
The article presents the results of the high biological efficiency of the drug Alben among the anthelmintic drugs Mebendazole (10%), Fenbendazole (22%) and Alben (20%) used against fish ligulidosis.